Anti-thrombocytopenic Activities of 15 Selected Indonesian Medicinal Plants: Psidium guajava Leaves, Phyllanthus niruri Aerial Parts, and Andrographis paniculata Leaves as Potential Sources in Enhancing Platelet Levels in Rats - Yasmiwar Susilawati; Ami Tjitraresmi; Ferry Ferdiansyah Sofian; Eli Halimah; Humaira Praswatika Dewi; Aria Aristokrat (The Prodia Education and Research Institute (PERI), 2025)
BACKGROUND: Thrombocytopenia is a medical condition characterized by a low platelet count in the blood, which can cause excessive bleeding and serious complications. Current conventional treatments for thrombocytopenia often present significant side effects and limitations, necessitating the exploration of alternative therapeutic options. Therefore, this study was conducted to evaluate the potential of Indonesian ethnomedicinal plants as alternative therapies.METHODS: The research was conducted by ethanol maceration of 15 medicinal plants selected based on their use in traditional Indonesian medicine to treat thrombocytopenia. Male white rats, aged three month and weighing between 150 and 250 g, were divided into four groups, which each group consists of five rats: the negative control group, group receiving 250 mg/kg BW extract, group receiving 500 mg/kg BW extract, and the normal control group. The effects of the test preparations on platelet count, erythrocyte count, and hematocrit were observed after 7 days of treatment.RESULTS: Among of 15 medicinal plants extract tested at a dose of 500 mg/kg BW, Psidium guajava L. leaves extract showed to increase blood platelets counts in thrombocytopenic mice by 60.82% (p<0.01) followed by Phyllanthus niruri L. aerial parts extract at (48.22%; p<0.01), and Andrographis paniculata (Burm.f.) Wall. ex Nees leaves extract (47.14%; p<0.01).CONCLUSION: The extracts of P. guajava leaves, aerial parts of P. niruri, and A. paniculata leaves exhibited significant potential in enhancing platelet levels. These findings suggest that some Indonesian medicinal plants can be used as alternative therapy for thrombocytopenia.KEYWORDS: dengue hemorrhagic fever, Phyllanthus niruri, Psidium guajava, Andrographis paniculata, thrombocytopenia